The Comparison Between Kerinci Siulak and Kerinci Rawang Dialect - Helmita Helmita; Nawa Vina Rahayu Anggriani (Jurnal Ilmiah Langue and Parole, 2022)
The Kerinci dialect has various variations in almost every region. These dialects also have differences, both at the phonological and lexical levels between dialects. However, speakers and interlocutors understand each other when speaking in their respective dialects so that it does not prevent the Kerinci people from communicating with each other. The purpose of the research was to describe the differences in language variation between the Kerinci Siulak dialect and the Kerinci Rawang dialect. This research uses Jeff Siegel's theory of language and dialect variations. In reviewing the data of this study using qualitative methods, while data collection used interview methods with recording techniques. This research was conducted in Hamparan Rawang Village and in Siulak Village, Kerinci Regency with 5 informants. The results showed that based on the available data, in the Kerinci language, the Siulak dialect and the Rawang dialect, there are sounds which are phonemes that can be grouped into three groups, namely vowels, diphthongs, and consonants. The Siulak and Rawang dialects have 23 sounds, with 5 vowels, 10 consonants, and 8 diphthongs. The correspondence phonemes of the two dialects are 35 which are at the initial, middle and final syllable caused by geographical, sociocultural and social status factors.